Clinical Evaluation of Tiletamine-Zolazepam CRI with Isoflurane Anesthesia in Dog - Patil, Harshwardhan Chandrakant; Chepte, Sharad Dnyandeo; Ali, S Sajid; Jadhav, Nitin Dadarao; Karad, Ganesh Govindrao (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
The study was conducted to evaluate two anesthetic protocols in 12 clinical cases of dogs presented to Veterinary Clinical Complex, COVAS, Parbhani for elective surgeries. These cases were divided into two equal groups (n=6). In both groups, dogs were pre-medicated with inj. Xylazine @ 1 mg/kg intramuscularly and anaesthesia was induced with inj. Tiletamine- Zolazepam (2 mg/kg) intravenously. Anaesthesia was maintained on constant rate infusion (CRI) of Tiletamine-Zolazepam (@ 2 mg/kg/h) in the dogs of group 1 and on Isoflurane in the dogs of group 2. Anaesthesia was assessed based on the quality of induction and recovery time in both groups. Clinico-physiological and haemato-biochemical parameters were measured in both groups at 5 different intervals. The induction score was identical in both groups with prolonged recovery in group 1. Clinico-physiological and haemato-biochemical values were changed from the base line value and return towards the baseline at recovery in both groups.
Keywords: Constant rate infusion (CRI); Dog; Isoflurane; Tiletamine- Zolazepam; Zoletil